A case report of symptomatic presacral myelolipoma. Issue 15 (April 2018) - Cho, Min Ho; Mandaliya, Rohan; Liang, John; Patel, Mitesh
Abstract: Rationale: Extra-adrenal myelolipoma in the presacral area often raises a concern for liposarcoma because they have similar radiologic features. Patient concerns: A 70-year-old woman with multiple abdominal surgeries in the past presented with persistent lower abdominal pain and anemia. A presacral mass, found on a pelvic magnetic resonance image (MRI), was suspicious of liposarcoma, as it is the most common fat containing mass in the presacral area. It is often difficult to make a diagnosis of myelolipoma just based on the radiological studies, which necessitates a histopathologic examination of the resected mass for a definitive diagnosis. Diagnoses: Myelolipoma is an encapsulated, benign tumor containing mature adipocytes and hematologic cells. Most of the patients with myelolipoma remain asymptomatic but continued growth of tumor without local invasion can lead to compression of nearby structures, causing persistent pain. Interventions: Asymptomatic patients do not require intervention but surgical resection is indicated for persistent pain or hemorrhage inside the tumor. Our patient had 2 indications for surgery – persistent pain as well as a provisional diagnosis of liposarcoma. After the surgical resection, pelvic pain was resolved, and a diagnosis of myelolipoma was made based on histopathologic examination. Outcomes: Patient was reassured that it was myelolipoma, a benign tumor, not requiring subsequent surveillance for recurrence. Lessons: Despite advancement in imaging techniques, and knowledge of the radiological features of myelolipoma, it still remains as a challenge for clinicians to make the distinction between liposarcoma and myelolipoma only based on diagnostic radiology. Although myelolipoma is a benign tumor, if patient suffers from persistent pain due to local mass effect, surgical resection is required.